Enteropathogenicity of Plesiomonas shigelloides and Aeromonas spp. in experimental mono- and coinfection with Cryptosporidium parvum in the intestine of neonatal BALB/c mice - Vitovec, J; Aldova, E; Vladik, P; Krovacek, K (Comparative immunology, microbiology and infectious diseases, 2001)
Enteropathogenicity of Plesiomonas shigelloides, Aeromonas hydrophila, A. caviae and A. sobria was studied both in monoinfections and in coinfections with coccidium Cryptosporidium parvum in neonatal BALB/c mice. In monoinfection experiments, neonatal BALB/c mice were orally infected with 7 x 10(7) or 7 x 10(8) CFU, respectively, of a strain of P. shigelloides or a strain of an Aeromonas spp. In coinfection experiments, the neonatal mice were, in addition to being orally infected with one of the four bacterial species, orally infected with an inoculum containing 10(5) oocysts of C. parvum. Results from monoinfections with P. shigelloides revealed long-term colonisation of the neonatal mouse intestine by this pathogen, along with associated pathological lesions. The lesions varied in severity from atrophy to necrosis of the mucosal inner surface of the ileum and colon, with predilection to the colon and brush border of colonic enterocytes. The effects of coinfection of P. shigelloides with C. parvum were characterised by bacteremia and heavy colonisation of the intestine by P. shigelloides. In addition, extensive necrotising inflammatory changes in the ileum and colon were accompanied by diarrhoea and deaths of coinfected mice. In contrast, the results from monoinfections of neonatal mice with Aeromonas spp. showed only a short-term colonisation of the intestine by the pathogen. However, when mice were coinfected with A. hydrophila and C. parvum, then the growth of the bacterial species was prolonged, and occurred in both the spleen and intestine. However, no substantial clinical or histopathological changes were observed in mice, whether monoinfected with Aeromonas spp. or coinfected with C. parvum. Our study suggests that experimental monoinfections of neonatal BALB/c mice with P. shigellodes, Aeromonas spp. and C. parvum, together with coinfections (each bacterial species with the protozoan C. parvum), may serve as a useful model to study the initial steps of gastrointestinal colonisation and diarrhoeal disease syndromes caused by enteropathogenic bacteria and protozoa, individually and in combination.
Keywords: Gram-Negative Bacterial Infections; Intestines; Mice; novorozená zvířata; Animals, Newborn; Cryptosporidium parvum; gramnegativní bakteriální infekce; Plesiomonas; Animals; Aeromonas; Cryptosporidiosis; kryptosporidióza; střeva; myši; zvířata